2015
DOI: 10.1007/s10337-015-2893-z
|View full text |Cite
|
Sign up to set email alerts
|

SDS-PAGE as a Tool for Hydrodynamic Diameter-Dependent Separation of Quantum Dots

Abstract: range 0-4 mM was used to improve visualization of QDs with diameters in the range from 7 ± 2 to 4 ± 2 nm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 45 publications
(47 reference statements)
1
10
0
Order By: Relevance
“…CGE is a sensitive, high‐throughput and high‐resolution system and has been used as a routine separation technique for size‐based analysis of nucleic acid , monoclonal antibodies and other types of proteins .…”
Section: Mode Of Separationmentioning
confidence: 99%
“…CGE is a sensitive, high‐throughput and high‐resolution system and has been used as a routine separation technique for size‐based analysis of nucleic acid , monoclonal antibodies and other types of proteins .…”
Section: Mode Of Separationmentioning
confidence: 99%
“…Absolute values were calculated using the standard samples (quinine sulfate), with known fluorescence QY value, according to the following Eq. [37]:…”
Section: Determination Of Quantum Yields (Qy)mentioning
confidence: 99%
“…Krizkova et al reported that they qualitatively measured NP sizes using agarose gel electrophoresis and sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE). 28 They used SDS-PAGE to separate different sized NPs using similar processes such as traditional NP purification with gel electrophoresis tools. 28 In this study, we have developed a new protocol using SDS-PAGE combined with fluorescence imaging for the detection and quantification of Zinkicide dissolution in aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
“…28 They used SDS-PAGE to separate different sized NPs using similar processes such as traditional NP purification with gel electrophoresis tools. 28 In this study, we have developed a new protocol using SDS-PAGE combined with fluorescence imaging for the detection and quantification of Zinkicide dissolution in aqueous solutions. The protocol was developed on the premise that Zinkicide particle sizes are comparable to protein dimensions and that they exhibit fluorescent properties when exposed to UV light, which is compatible with conventional gel imaging stations.…”
Section: Introductionmentioning
confidence: 99%